Serial dependence does not originate from low-level visual processing - Ceylan, Gizay; Herzog, Michael H.; Pascucci, David (Cognition, 2021)
Perception depends not only on the current sensory input but also on the preceding history of stimuli. In serial dependence (SD), for example, the orientation of a Gabor patch is mistakenly reported as more similar to previous trials than it actually is. This bias is typically observed for moderate orientation differences (<45°) and extends over a few trials in the past. It is hotly debated whether SD originates at perceptual or post-perceptual, e.g., decisional, stages. Here, we provide evidence for the latter hypothesis. We presented Gabor patches with different spatial frequencies or Gabors intermingled with dot patterns. Even though stimuli were perceptually clearly dissimilar, we found robust SD effects arguing against any perceptual account. These findings suggest a re-evaluation of current models and theoretical accounts of SD.